Selection of optimal intensity measures in probabilistic seismic demand models of highway bridge portfolios. - Padgett, Jamie E. (Earthquake engineering & structural dynamics.)
Probabilistic seismic demand models are a common and often essential step in generating analytical fragility curves for highway bridges. With these probabilistic models being traditionally conditioned on a single seismic intensity measure (IM), the degree of uncertainty in the models is dependent on the IM used. Selection of an optimal IM for conditioning these demand models is not a trivial matter and has been the focus of numerous studies. Unlike previous studies that consider a single structure for IM selection, this study evaluates optimal IMs for use when generating probabilistic seismic demand models for bridge portfolios such as would be found in HAZUS-MH. Selection criteria such as efficiency, practicality, sufficiency, and hazard computability are considered in the selection process.